34 Screening for cervical cancer in women under the age of 25: a cross-sectional study at an university hospital in minas gerais – Brazil. (13th November 2020) - Barbosa, L; Napoleão, B; Franco, M; Ferreira-Filho, E; Nicolau, S
Abstract : The main risk factor for cervical cancer (CC) is persistent infection by oncogenic types of human-papillomavirus. This infection promotes cellular changes leading to the emergence of pre-neoplastic lesions that, if left untreated, can progress to invasive neoplasia. In Brazil, screening programs that aim to detect these CC precursor lesions through cervical cytology are recommended only for women between 25 and 64 years old, who have had at least one sexual intercourse. This study aims to evaluate the histological diagnoses and the frequency of patients under 25 years of age who were referred to colposcopy due to altered colpocytologies; and the distribution of high-grade lesions according to age. Method: Cross-sectional study, with retrospective data collection from medical records of asymptomatic patients between 15 and 24 years old referred to the Hospital das Clínicas Samuel Libânio due to changes in the screening test (pap smear). Result: Among the 4, 527 women aged 15 to 24 years, 304 (6.7%) had abnormal cytologies, 73 of whom (24%) were referred for colposcopy. Biopsy was performed in 63 patients. Approximately 65% of high-grade lesions (CIN 2+) were in the 21- to 24-year age range, including one case of 'in situ' carcinoma and one case of invasive squamous carcinoma. Conclusion: The highest rate of high-grade lesion was found in the 21–24 age group. This highlights the importance of reevaluating the indication for CC screening in younger women. Furthermore a better understanding of the risk factors involved in the evolution of these lesions in young patients is necessary.